(untitled) (CSIAM Transactions on Applied Mathematics, 2023)
We improve Gilbert-Varshamov bound by graph spectral method. Gilbert graph G_q,n,d is a graph with all vectors in F^n_q as vertices where two vertices are adjacent if their Hamming distance is less than d. In this paper, we calculate the eigenvalues and eigenvectors of G_q,n,d using the properties of Cayley graph. The improved bound is associated with the minimum eigenvalue of the graph. Finally we give an algorithm to calculate the bound and linear codes which satisfy the bound.